In vivo Calcium Imaging of Evoked Calcium Waves in the Embryonic Cortex - Yuryev, Mikhail; Pellegrino, Christophe; Jokinen, Ville; Andriichuk, Liliia; Khirug, Stanislav; Khiroug, Leonard; Rivera, Claudio (Frontiers in Cellular Neuroscience, 2016)
The dynamics of intracellular calcium fluxes are instrumental in the proliferation, differentiation and migration of neuronal cells. Knowledge thus far of the relationship between these calcium changes and physiological processes in the developing brain has derived principally from ex vivo and in vitro experiments. Here, we present a new method to image intracellular calcium flux in the cerebral cortex of live rodent embryos, whilst attached to the dam through the umbilical cord. Using this approach we demonstrate induction of calcium waves by laser stimulation. These waves are sensitive to ATP-receptor blockade and are significantly increased by pharmacological facilitation of intracellular-calcium release. This approach is the closest to physiological conditions yet achieved for imaging of calcium in the embryonic brain and as such opens new avenues for the study of prenatal brain development. Furthermore, the developed method could open the possibilities of preclinical translational studies in embryos particularly important for developmentally related diseases such as schizophrenia and autism.